2005
DOI: 10.1002/mrdd.20051
|View full text |Cite
|
Sign up to set email alerts
|

Prechtl's assessment of general movements: A diagnostic tool for the functional assessment of the young nervous system

Abstract: General movements (GMs) are part of the spontaneous movement repertoire and are present from early fetal life onwards until the end of the first half a year of life. GMs are complex, occur frequently, and last long enough to be observed properly. They involve the whole body in a variable sequence of arm, leg, neck, and trunk movements. They wax and wane in intensity, force and speed, and they have a gradual beginning and end. Rotations along the axis of the limbs and slight changes in the direction of movement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
598
0
37

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 573 publications
(670 citation statements)
references
References 45 publications
5
598
0
37
Order By: Relevance
“…The most reliable method to evaluate the integrity of the central nervous system of young infants is to assess the quality of their spontaneous motor repertoire (Einspieler and Prechtl 2005). Around the age of 3 months, the infant's motor repertoire is characterized by so-called fidgety movements (FMs) that are highly predictive of neurological outcome .…”
Section: Assessment Of Spontaneous Motor Repertoirementioning
confidence: 99%
See 1 more Smart Citation
“…The most reliable method to evaluate the integrity of the central nervous system of young infants is to assess the quality of their spontaneous motor repertoire (Einspieler and Prechtl 2005). Around the age of 3 months, the infant's motor repertoire is characterized by so-called fidgety movements (FMs) that are highly predictive of neurological outcome .…”
Section: Assessment Of Spontaneous Motor Repertoirementioning
confidence: 99%
“…From patient 2, video recordings were made during an outpatient visit at the age of 10 weeks and 1 day and at the age of 14 weeks and 1 day. The recordings were made during a period of active wakefulness with the infant lying supine and lasted 10 min (Einspieler and Prechtl 2005). Certified author MMH analyzed the recordings off-line according to Prechtl's method ) and blinded for the outcome.…”
Section: Assessment Of Spontaneous Motor Repertoirementioning
confidence: 99%
“…The first and most important finding of our study was that HC infants had a higher MOS at 3 months after term than DXM infants. Previously, Einspieler et al reported that impairment of the quality of the motor repertoire, especially around 3 months after term, is highly predictive of severe neurological sequelae (11,13). Of the five items on the Motor Optimality List, FM quality is the most reliable predictor of either severe neurological abnormalities or a normal neurological outcome (13,16).…”
Section: Discussionmentioning
confidence: 99%
“…The qualitative assessment of general movements (GMs) from video recordings is a sensitive, noninvasive method to investigate the integrity of the young infant's brain (10,11). This method is based on visual Gestalt perception of GM quality up to 5 months after term.…”
mentioning
confidence: 99%
“…These latter, spontaneous arm movements are self‐generated by the infant, they are endogenous, they come from within. And they can be useful in specialized clinical assessments of neuropsychological integrity as well as to become a reference point to assist maternal bonding through recognition of an infant's agency (Brazelton & Nugent, 1995; Einspieler & Prechtl, 2005; Spittle, Doyle, & Boyd, 2008). But these self‐generated “general movements” of infants are not well studied in psychology.…”
Section: Introductionmentioning
confidence: 99%